Essential oils of Psidium cattleianum Sabine leaves and flowers: Anti-inflammatory and cytotoxic activities - Elsayed, Heba E.; El-Deeb, Eman M.; Taha, Heba; Taha, Hussein S.; Elgindi, Mohamed R.; Moharram, Fatma A. (Frontiers in Chemistry, 2023)
Psidium cattleianum Sabine is a Brazilian native shrub, cultivated for its edible fruits, known as araçá (strawberry guava). Cattleianum is recognized for health and food applications, though the essential oil (EOs) from the Egyptian inhabitant is not been fully explored. The current study investigated the anti-inflammatory and cytotoxic activities P. cattleianum leaves and flowers EOs. Among other methods, the supercritical fluid extraction offered the highest yield, 0.62 % (leaves) and 1.4% (flowers). GC/MS identified β-caryophyllene and α-humulene in both organs with high, but variable percentages. The leaves demonstrated strong activity in inhibiting the 5-lipoxygenase enzyme (IC50 2.38), while the flowers in inhibiting COX-2 (IC50 2.575). The leaves showed potent, selective cytotoxicity to MCF-7 cells (IC50 5.32) via apoptosis by modulating the p53/Bax/Bcl2 axis. The deduced activities are possible due to the synergism between the volatile components that endorse P. cattleianum leaves EOs in the management of breast cancer and inflammatory disorders